Duration of COVID-19 Infectious Agent Positivity in the Postmortem Process - Ünüvar Göçeoğlu, Ümit; Balcı, Yasemin; Togan, Turhan; Aksözek, Alper; Gürsoy, Canan; Çitil, Burak Ekrem; Gök Çatal, Yeşim; Ekinci, Ecesu (The Bulletin of Legal Medicine, 2023)
Objective: Studies show that in patients diagnosed with Coronavirus disease-2019 (COVID-19), polymerase chain reaction (PCR) tests can give false negative results depending on sampling techniques/regions. In this study; the positivity of virus RNA was studied consecutive lung tru cut needle biopsy taken at 6-hour intervals in cases who died during treatment due to COVID-19 infection, it was aimed to determine the postmortem safe working range. Methods: 21 patients who died during treatment due to COVID-19 infection diagnosed with clinical and/or RNA detection were included. Antemortem, postmortem swabs results, and virus RNA detection by PCR made from postmortem lung tissue samples were compared with their clinics. Results: Fifteen (71.4%) of 21 cases were male and 6 (28.6%) were female. The mean age is 71.9 (standard deviation=12.079). All of the toracic CT findings at hospitalization had a ground-glass opacity. The mean hospitalization time was 11.7 days. Antemortem nasopharyngeal virus positivity was shown in 13 cases (61.9%), postmortem nasopharyngeal virus positivity in 5 cases (23.8%), and virus positivity in lung tissue samples in 7 cases (33.3%). No significant correlation was found virus positivity in nasopharyngeal swab and lung tissue sample, the incompatibility rate was 19.1%, which was statistically significant. Conclusion: Although the targeted sample size could not be reached due to study limitations, the inconsistency in virus positivity in nasopharyngeal swabs and lung tissue samples is significant. It is certain that studies with a large comparative sample are needed in terms of postmortem survival time, clinical and organ damage caused by the virus.